2009
DOI: 10.1051/cocv/2009033
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent formulation and numerical analysis of a fire confinement problem

Abstract: Abstract.We consider a class of variational problems for differential inclusions, related to the control of wild fires. The area burned by the fire at time t > 0 is modelled as the reachable set for a differential inclusionẋ ∈ F (x), starting from an initial set R0. To block the fire, a barrier can be constructed progressively in time. For each t > 0, the portion of the wall constructed within time t is described by a rectifiable set γ(t) ⊂ R 2 . In this paper we show that the search for blocking strategies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…As proved in [9], under the assumptions (A1)-(A3) the two formulations are equivalent. In particular, if t → γ(t) is a complete, optimal strategy for (OP1), then the rectifiable set…”
Section: An Equivalent Formulationmentioning
confidence: 92%
See 4 more Smart Citations
“…As proved in [9], under the assumptions (A1)-(A3) the two formulations are equivalent. In particular, if t → γ(t) is a complete, optimal strategy for (OP1), then the rectifiable set…”
Section: An Equivalent Formulationmentioning
confidence: 92%
“…Indeed, for each t ≥ 0 one needs to describe the portion of the wall constructed within time t. The subsequent paper [9] showed that the both the blocking problem and the optimization problem can be reformulated in a simpler way, where an admissible strategy is determined by one single rectifiable set Γ ⊂ IR 2 . This approach is particularly useful for the numerical computation of optimal strategies.…”
Section: An Equivalent Formulationmentioning
confidence: 99%
See 3 more Smart Citations